Facile processes for producing robust, transparent, conductive platinum nanofiber mats. Issue 18 (26th April 2017) - An, Seongpil; Kim, Yong Il; Sinha-Ray, Sumit; Kim, Min-Woo; Jo, Hong Seok; Swihart, Mark T.; Yarin, Alexander L.; Yoon, Sam S.
Abstract : A highly catalytic, bendable, stretchable, transparent platinum nanofiber mat. Abstract : Mechanically robust freestanding platinum (Pt) nanofiber (NF) meshes are of great interest in applications where the corrosion resistance, malleability, and stability of a pure platinum structure must be combined with high surface area for catalysis. For photoelectrochemical applications, transparent electrodes are desirable. Several 1-dimensional (1D) Pt-based materials have been developed, but energy-intensive fabrication techniques and unsatisfactory performance have limited their practical implementation in next-generation photoelectrochemical applications. Here, we introduce relatively simple yet commercially-viable methods for creating robust, free-standing PtNF mats through combined electrospinning/solution blowing and electroplating steps. The PtNFs obtained by these processes exhibited outstanding low sheet resistance ( R s ) values with reasonable transparency. In addition, the PtNFs were highly bendable and stretchable. Thus, the new methods and materials presented here hold great promise for creating mechanically robust and catalytically active transparent conducting films for diverse photoelectrochemical applications.